Framing the penal colony: representing, interpreting and imagining convict transportation - Fuggle, Sophie; Forsdick, Charles; Massing, Katharina (Palgrave studies in crime, media and culture, 2023)
This book examines the representation of penal colonies both historically and in contemporary culture, across an array of media. Exploring a range of geographies and historical instances of the penal colony, it seeks to identify how the ‘penal colony’ as a widespread phenomenon is as much ‘imagined’ and creatively instrumentalized as it pertains to real sites and populations. It concentrates on the range of ‘media’ produced in and around penal colonies both during their operation and following their closures. This approach emphasizes the role of cross-disciplinary methods and approaches to examining the history and legacy of convict transportation, prison islands and other sites of exile. It develops a range of methodological tools for engaging with cultures and representations of incarceration, detention and transportation. The chapters draw on media discourse analysis, critical cartography, museum and heritage studies, ethnography, architectural history, visual culture including film and comics studies and gaming studies. It aims to disrupt the idea of adopting linear histories or isolated geographies in order to understand the impact and legacy of penal colonies. The overall claim made by the collection is that understanding the cultural production associated with this global phenomenon is a necessary part of a wider examination of carceral imaginaries or ‘penal spectatorship’ (Brown, 2009) past, present and future. It brings together historiography, criminology, media and cultural studies. Sophie Fuggle is Associate Professor of Postcolonial Studies and Cultural Heritage at Nottingham Trent University, UK, and teaches on the MA in Museum and Heritage Development programme. Charles Forsdick is James Barrow Professor of French at the University of Liverpool, UK. He has published on a range of subjects, including travel writing, colonial history, postcolonial and world literature, and the memorialisation of slavery. Katharina Massing is Senior Kecturer at Nottingham Trent University, UK and Course Leader of the MA in Museum and Heritage Development programme. .